Venous Thromboembolism in Hospitalized COVID-19 Patients. (November 2020) - Sridharan, Gurusaravanan Kutti; Vegunta, Radhakrishna; Rokkam, Venkata Ram Pradeep; Meyyur Aravamudan, Veeraraghavan; Vegunta, Rathnamitreyee; Khan, Shahab R.; Ponnada, Suresh; Boregowda, Umesha; Prudhvi, Kalyan; Chamarthi, Gajapathiraju; Mohan, Babu P.
Abstract : Background: Venous thromboembolism (VTE) is increasingly reported in seriously ill patients with COVID-19 infection. Incidence of VTE has been reported before and results varied widely in study cohorts. Area of uncertainty: Incidence of major VTE (segmental pulmonary embolism and above and proximal deep vein thrombosis) which is a contributor to mortality and morbidity is not known. Also, data is unclear on the optimal anticoagulation regimen to prevent VTE. Data sources: Multiple databases including PubMed were searched until May 12, 2020, to include studies reporting VTE in hospitalized COVID-19 adult patients. MOOSE guidelines were followed in selection, and 11 studies were included. We conducted a systematic review and meta-analysis to quantitatively assess the VTE burden in hospitalized COVID-19 patients and potential benefits of therapeutic dosing of anticoagulation compared with prophylaxis dosing for VTE prevention. Therapeutic advances: Many societies and experts recommend routine prophylactic anticoagulation with heparin for VTE prevention in hospitalized COVID-19 patients. In this meta-analysis, the pooled rate of major VTE was 12.5% in hospitalized patients and 17.2% in intensive care unit patients. When therapeutic anticoagulation dosing was compared with prophylactic anticoagulation, the pooled odds ratio of VTE was 0.33 (95% confidence interval 0.14–0.75; P = 0.008, I 2 = 0%) suggesting statistical significance with therapeutic dosing of anticoagulation for primary prevention of VTE in all hospitalized patients. However, this should be interpreted with caution as the bleeding events and safety profile could not be ascertained because of lack of adequate information. We recommend applying this finding to hospitalized COVID 19 patients only after carefully weighing individual bleeding risks and benefits. Conclusion: Major VTE events, especially pulmonary embolism, seem to be high in COVID-19 patients admitted to the intensive care unit. Therapeutic anticoagulation dosing seems to significantly benefit the odds of preventing any VTE when compared with prophylactic dosing in all hospitalized patients. Abstract : Supplemental Digital Content is Available in the Text.